Prediction of Chlamydia pneumoniae protein localization in host mitochondria and cytoplasm and possible involvements in lung cancer etiology: a computational approach - Aws Alshamsan; Shahanavaj Khan; Ahamad Imran; Ibrahim A. Aljuffali; Khalid Alsaleh (Elsevier, 2017)
Collecting evidence suggests that the intercellular infection of Chlamydia pneumoniae in lungs contributes to the etiology of lung cancer. Many proteins of Chlamydia pneumoniae outmanoeuvre the various system of the host. The infection may regulate various factors, which can influence the growth of lung cancer in affected persons. In this in-silico study, we predict potential targeting of Chlamydia pneumoniae proteins in mitochondrial and cytoplasmic comportments of host cell and their possible involvement in growth and development of lung cancer. Various cellular activities are controlled in mitochondria and cytoplasm, where the localization of Chlamydia pneumoniae proteins may alter the normal functioning of host cells. The rationale of this study is to find out and explain the connection between Chlamydia pneumoniae infection and lung cancer. A sum of 183 and 513 proteins were predicted to target in mitochondria and cytoplasm of host cell out of total 1112 proteins of Chlamydia pneumoniae. In particular, many targeted proteins may interfere with normal growth behaviour of host cells, thereby altering the decision of program cell death. Present article provides a potential connection of Chlamydia pneumoniae protein targeting and proposed that various targeted proteins may play crucial role in lung cancer etiology through diverse mechanisms. Keywords: Lung cancer, Chlamydia pneumoniae, Etiology, Systems biology, Protein targeting